Silent footsteps - Bannister, Jo (Bannister, Jo. Gabriel Ash and Hazel Best mysteries, 2019)
"When does a secret admirer become a stalker? When chocolates on the doorstep give way to the sound of an intruder on the stairs? When the victim's friends are waylaid in the dark and beaten bloody? When she receives photographs memorializing these events? Or when people start dying? For Constable Hazel Best, the pivot point is the attack on her friend Gabriel Ash. That's when she focuses all her ingenuity on finding the man responsible. Her police colleagues would be more help if they weren't already occupied with two murders - but assistance does arrive from an unexpected source. In the end, though, Hazel must deal with the stalker alone. And more than her own life will depend on the outcome."--Publisher's description.